PENGARUH PEMBERIAN PROBIOTIK EM4 TERHADAP PERTUMBUHAN BERAT BADAN DAN FCR AYAM BROILER - Moh.Ghoziuddin Silmi; Rico Anggriawan; Diyah Ayu Candra (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2025)
The livestock sector plays an important role in national development, particularly in ensuring the availability of animal protein sources for all Indonesian people. Among various livestock products, meat is the most popular commodity, with broiler chickens being a type of poultry with a high meat production capacity. In this study, a Completely Randomized Design (CRD) was applied, dividing the subjects into four different treatment groups, with three replications for each group. The research findings showed the average individual weight in the different probiotic treatment categories during the third and fifth weeks, along with the average weight gain and standard deviation. Compared to the group that did not receive probiotics, this study demonstrated that chickens given probiotics had higher body weight, and although body weight and feed conversion efficiency increased, the amount of feed consumed did not differ significantly between the group given probiotics and the control group. Thus, probiotics play a role in improving feed utilization efficiency without affecting the amount of feed consumed.